Analysis of Gait Motion Changes by Intervention Using Robot Suit Hybrid Assistive Limb (HAL) in Myelopathy Patients After Decompression Surgery for Ossification of Posterior Longitudinal Ligament - Ezaki, Seioh; Kadone, Hideki; Kubota, Shigeki; Abe, Tetsuya; Shimizu, Yukiyo; Tan, Chun Kwang; Miura, Kousei; Hada, Yasushi; Sankai, Yoshiyuki; Koda, Masao; Suzuki, Kenji; Yamazaki, Masashi (Frontiers in Neurorobotics, 2021)
Ossification of the posterior longitudinal ligament (OPLL) is a hyperostonic condition in which the posterior longitudinal ligament becomes thick and loses its flexibility, resulting in ectopic ossification and severe neurologic deficit (Matsunaga2012). It commonly presents with myelopathy and radiculopathy and with myelopathy progression motor disorders and balance disorders can appear. Even after appropriate surgical decompression, some motor impairments often remain. The Hybrid Assistive Limb (HAL) is a wearable powered suit designed to assist and support the user’s voluntary control of hip and knee joint motion by detecting bioelectric signals from the skin’s surface and force/pressure sensors in the shoes during movement. In the current study, the HAL intervention was applied to 15 patients diagnosed with OPLL who presented with myelopathy after decompression surgery (6 acute and 9 chronic stage). Following the HAL intervention, there were significant improvements in gait speed, cadence, stride length, in both acute and chronic groups. Joint angle analysis of the lower limbs showed that range of motion (ROM) of hip and knee joints in acute group, and also ROM of hip joint and toe-lift during swing in chronic group increased significantly. ROM of knee joint became closer to healthy gait in both groups. Electromyography analysis showed that hamstrings activity in the late swing phase increased significantly for acute patients. Immidiate effect from HAL session was also observed. EMG of vastus medialis were decreased except chronic 7th session and EMG of gastrocnemius were decreased except acute 7th session, which suggests the patients were learning to walk with lesser knee-hypertension during the session. After all, double knee action appeared in both acute and chronic groups after the HAL intervention, rather than knee hyper-extension which is a common gait impairment in OPLL. We consider that, together, these improvements lead to a smoother and healthier gait motion.